Mandalas as a Source of Self-Expression - Miłek, Katarzyna; İPEK, Jale; Breś, Anna (Future Science / FSH-PH Publications, 2024)
The article is a presentation of the meaning and characteristics of mandalas that derive from Sanskrit symbolism. The Kabbalistic overtones of their compositions intrigued early psychoanalysts. They have been assimilated to treat and calm patients suffering from neurosis, psychosis, depression. They were seen as expressive, diagnostic and therapeutic. The article presents different views on the values and effects of the use of mandalas in education, relaxation and therapy. Due to the lack of scientific premises for use, relaxation use is encouraged during rehabilitation, after-school and speech therapy classes. A substantive approach to the subject encourages the search for applications in education in various fields, but this requires undertaking scientific research and verification of applications. The article is an exhaustive analysis of the literature on the use of mandalas.